1995
DOI: 10.1128/iai.63.5.1899-1905.1995
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the structure of glucuronoxylomannan in isolates from patients with recurrent cryptococcal meningitis

Abstract: Capsular glucuronoxylomannans (GXM) of Cryptococcus neoformans var. neoformans isolates from patients with recurrent cryptococcal meningitis were analyzed by 1 H nuclear magnetic resonance spectroscopy and for reactivity with factor sera (Iatron, Tokyo, Japan). For each patient the initial and relapse isolates had previously been shown to be indistinguishable by DNA restriction fragment length polymorphism analysis. For patients J11 and J22 the GXM of the initial and relapse isolates were identical. For patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…For C. neoformans strain 24067, analysis of different isolates maintained in different laboratories has revealed striking differences in phenotypic characteristics and virulence Chen & Casadevall, 1999). Several observations support the concept that microevolution of C. neoformans also occurs during the course of human infection and contributes to persistence of infection: (1) serial C. neoformans isolates from chronically infected HIV-positive patients demonstrated differences in murine infection models as well as changes in the polysaccharide capsule (Cherniak et al, 1995;Jain, 2005); (2) investigations in chronic murine infection models have documented the emergence of both giant cells and poorly encapsulated forms (Feldmesser et al, 2001); (3) the emergence of variants that exhibit changes of the sterol content in the cell membrane has been demonstrated (Currie et al, 1995); and (4) changes in colony morphology and karyotype pattern occur during chronic infection (Fries et al, 1996;Sukroongreung et al, 2001). In addition, careful analysis of primary clinical specimens has shown that phenotypic variation in colony morphology can be observed in isolates from the spinal fluid .…”
Section: Microevolution and Phenotype Variability During Chronic Crypmentioning
confidence: 89%
“…For C. neoformans strain 24067, analysis of different isolates maintained in different laboratories has revealed striking differences in phenotypic characteristics and virulence Chen & Casadevall, 1999). Several observations support the concept that microevolution of C. neoformans also occurs during the course of human infection and contributes to persistence of infection: (1) serial C. neoformans isolates from chronically infected HIV-positive patients demonstrated differences in murine infection models as well as changes in the polysaccharide capsule (Cherniak et al, 1995;Jain, 2005); (2) investigations in chronic murine infection models have documented the emergence of both giant cells and poorly encapsulated forms (Feldmesser et al, 2001); (3) the emergence of variants that exhibit changes of the sterol content in the cell membrane has been demonstrated (Currie et al, 1995); and (4) changes in colony morphology and karyotype pattern occur during chronic infection (Fries et al, 1996;Sukroongreung et al, 2001). In addition, careful analysis of primary clinical specimens has shown that phenotypic variation in colony morphology can be observed in isolates from the spinal fluid .…”
Section: Microevolution and Phenotype Variability During Chronic Crypmentioning
confidence: 89%
“…The present study demonstrated that the 3-linked mannan backbone is the common scaffold to which the anionic substituents are attached. Polysaccharides with a 3-linked mannan backbone are relatively rare in nature, but substituted a-1,3-linked mannans have been reported in the fruiting bodies of some fungi and as lipopolysaccharides in some mycobacteria (Ogawa and Yamamoto 1985, Cherniak et al 1995, Senchenkova et al 1997, Ichikawa et al 2001, Guérardel et al 2002. Interestingly, the substitution patterns of the mannan backbone in several of these polysaccharides bear some similarities to those of the diatom mannans, with GlcpA and Xylp substitutions attached at O-2 of approximately every second 3-linked Manp residue.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon also occurred with IgG and F(ab) 2 fragments, and consequently IgG phagocytosis occurred through both Fc and CR receptors even in the absence of complement (Netski and Kozel, 2002). As the capsular polysaccharide of C. gattii is more highly substituted than that of the other varieties (Cherniak et al, 1995) we sought to establish whether antibody-mediated complement-independent phagocytosis through CR also occurred with this variety, especially when considering comparative studies of macrophage fungal cell interactions involving the different cryptococcal varieties and species. A dose-dependent relationship was observed with IgM mAb 12A1 in phagocytosis assays, whereby increasing concentrations of IgM promoted an increase in phagocytosis by J774.16 cells in the absence of complement ( Fig.…”
Section: Opsonization Of C Neoformans and C Gattiimentioning
confidence: 90%